Comparative market analysis and economic simulation for Morocco of the parabolic trough and dish CSP technologies - Lemmer, Veronika (2014)
Tese de mestrado integrado em Engenharia da Energia e do Ambiente, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2014